Male fertility: a review of the publications from April – June 2021 - D. S. Rogozin (Вестник урологии, 2021)
The article provides an overview of the most significant publications on the topic of male infertility. The main selection criteria were considered the practical significance of the article, as well as the impact factor of the journal in which it was published, according to the SCImago Journal Rank (SJR). As a result, a list of 10 works published in the II quarter (April – June) of 2021 was formed. The review includes articles on the following issues: the effectiveness of repeated micro-TESE in non-obstructive azoospermia, the role of COVID-19 in male fertility, the effect of testosterone therapy on spermatogenesis, testicular microlithiasis, electroejaculation as a method of obtaining spermatozoa, harm from carrying cell phones near the genitals, prediction of the effectiveness of intrauterine insemination, the effect of advanced paternal age on sperm aneuploidy, and the importance of the microbiome for male fertility.